Transforming the Preparation of Leaders into a True Partnership Model - Mary Devin (Educational Considerations, 2016)
In the early 2000s, as public education moved into the accountability era spawned by passage of No Child Left Behind in 2001, landmark research produced convincing evidence of the importance of leadership.
Keywords: Kansas State University; school superintendent; classroom instruction; leader; preparation; New Approach; Academy; experiences; students